Implementation Of Strengthening The Digital Economic Platform On Halal SMEs - Novi Primita Sari (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
With a large Muslim community in Malang City and the influx of digital technology which increased quite a lot during the Covid-19 pandemic, this research wants to describe and analyze how the existence of digital platforms supports the micro and small business sector in Malang City. The type of research carried out is descriptive quantitative research that uses literature studies and also primary data obtained from the questionnaire results for later testing and analysis. Based on the results of data processing using the smart PLS 3 application, it can be seen that of the 3 latent variables used, only 2 variables influence variable Y, namely variable X1 which is represented by Perceived Usefulness and variable X3, namely Perceived Ease To Use on Y, namely the total transaction that obtained by MSMEs while using digital economic tools as indicators